Monitoring and Evaluation Systems and Performance of Non-Governmental Based Maternal Health Projects in Bungoma South Sub-County, Kenya - Micah, Nalianya Japheth; Luketero, Stephen Wanyonyi (European Scientific Journal, ESJ, 2017)
The growth in number and size of non-governmental organizations in Kenya has been met with a growing concern about identifying their achievements and effectiveness of their projects. The struggle by majority of NGOs account for their work and demonstrate real results continues to taint their image as development change agents to various stakeholders. One way organizations can improve effectiveness of their interventions is by strengthening their monitoring and evaluation systems. This study sought to determine the influence of monitoring and evaluation systems on performance of non-governmental based maternal health projects in Bungoma South Sub-County, Kenya. Specific objectives were to: determine how monitoring and evaluation plans, human Resource capacity, nature of monitoring and evaluation information systems adopted, and stakeholder participation in monitoring and evaluation influence performance of nongovernmental maternal health projects in Bungoma South Sub-County. A descriptive survey design and correlation design was employed. With a target population of 101 respondents, a census was conducted on all respondents involved in implementation of maternal health projects from the three non-governmental organizations (AA, STC, and CREADIS). Data was collected through questionnaires and analyzed using descriptive statistics. A fairly strong correlation of 0.607, 0.530, 0.533 and -0.489 for monitoring and evaluation plans, human resource capacity, nature of information system adopted, and stakeholder participation respectively and performance of maternal health projects. The regression analysis indicated that, taking all the independent variables at a constant zero, performance of maternal health projects was 4.087. The study recommends alignment of staff job descriptions with their M&E plans, increase the number of M&E training, conduct Routine Data Quality Assessment to detect areas of difficulties to staff, invest in Information and Communication Technology, and manage stakeholders’ involvement in Monitoring and Evaluation in order to achieve quality data.